MLOps for containers with AWS and GCP - Deza, Alfredo (Pragmatic AI Solutions, 2021)
Learn to build MLOps predictions with containers * AWS App Runner * AWS ECR (EC2 Container Registry) * Flask * SKlearn * Google Cloud Run * Practical MLOps * MLOPs Cookbook.